2018
DOI: 10.1186/s12909-018-1239-6
|View full text |Cite
|
Sign up to set email alerts
|

Crossborder curriculum partnerships: medical students’ experiences on critical aspects

Abstract: BackgroundThe past decade has witnessed an upsurge in medical curriculum partnerships established across national boundaries to offer students at the foreign institution (host) a learning experience comparable to that of students at the exporting institution (home). However, since the learning environments and national healthcare contexts differ greatly between institutions, concerns have been raised in the literature about potential low quality of curriculum delivery, inadequate preparation of students to pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…[ 18 ] Waterval et al conducted a survey on cross-border curriculum of medical students and found that host students felt the partnership afforded opportunities to acquire unique academic competencies and boost their career. [ 19 ] Our findings are consistent with existing studies. Meanwhile, due to the difficulties of expenses, foreign language, and living habits while travelling abroad, introduction of international programs at native countries can benefit students of both native and foreign countries.…”
Section: Discussionsupporting
confidence: 93%
“…[ 18 ] Waterval et al conducted a survey on cross-border curriculum of medical students and found that host students felt the partnership afforded opportunities to acquire unique academic competencies and boost their career. [ 19 ] Our findings are consistent with existing studies. Meanwhile, due to the difficulties of expenses, foreign language, and living habits while travelling abroad, introduction of international programs at native countries can benefit students of both native and foreign countries.…”
Section: Discussionsupporting
confidence: 93%
“…The study found that the Inuit students faced a number of challenges, such as language barriers, cultural differences, and a lack of support from their families and communities. Waterval et al ( 41 ) explored the dynamics of international medical curriculum partnerships, noting the potential risks such as subpar curriculum execution and insufficient preparation for clinical practice in host nations. They underscore the necessity for further exploration into students’ perspectives on these transnational educational experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diverse backgrounds of students, explored by Mustonen and Strömmer ( 37 ) and Roshini et al ( 38 ), call for an inclusive, multilingual approach to education, recognizing and utilizing the linguistic assets of students. Stakeholder experiences, particularly of groups like the Inuit studied by Møller ( 40 ) and international students in curriculum partnerships examined by Waterval et al ( 41 ), reveal cultural and linguistic hurdles, yet also highlight the transformative potential of EMI in fostering global competencies. Finally, the critical role of language proficiency in academic success, as seen in the findings of Tenney et al ( 43 ) and Schoepp ( 44 ), reinforces the need for language support in EMI programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations